Effects of parasitism and environment on shell size of the South American intertidal mud snail Heleobia australis (Gastropoda) - Alda, Maria del Pilar (2010)
The aim of this work was to evaluate the effects of parasitism and certain environmental factors on the shell size of Heleobia australis (Hydrobiidae, Cochliopinae). We report sporocysts and metacercariae of Microphallus simillimus (Microphallidae, Trematoda) parasitizing the gonad and digestive gland of H. australis specimens from two sites of Bahía Blanca estuary, Argentina. The prevalence of infection was significantly higher (34.17% in winter and 68.14% in late spring) in snails from the outer estuary at Site 2 than in those from the inner estuary at Site 1 (5.88% and 4.71% respectively). The only known definitive host for this digenean is the white-backed stilt Himantopus melanurus (Recurvirostridae, Aves), most abundant in the estuary during winter. Parasitism by M. simillimus causes variations in the shell dimensions of H. australis, the shells of infected snails being narrower than those of uninfected snails. Snails from Site 2 were found in general to be significantly smaller than those at Site 1, possibly as a result of differences in environmental factors such as the degree of exposure to wave energy, the allocation of energy to reproduction rather than growth (induced by predation and/or parasitic castrators) and anthropogenic stressors.